2010
DOI: 10.1002/dc.21471
|View full text |Cite
|
Sign up to set email alerts
|

Glandular neoplasia and borderline endocervical reporting rates before and after conversion to the SurePathTM liquid‐based cytology (LBC) system

Abstract: Reporting rates for glandular neoplasia in 464,754 cervical samples reported at six laboratories in 12-month periods before and after the implementation of Surepath™ LBC processing are compared. The introduction of LBC processing is seen to have resulted in a significant (P = 0.001) increase in the detection rate for endocervical glandular neoplasia (from 2.2 per 10,000 tests to 3.9 per 10,000) while maintaining high levels of reporting specificity. An observed fall in the number of samples reported as showing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 23 publications
1
15
0
Order By: Relevance
“…It has been suggested that liquid-based cytology, which leads to a reduction of blood and inflammatory cells and better cellular and nuclear preservation, can improve the recognition and detection of EMCA [4,5,6]. However, there are only a small number of studies in the English literature on SurePath™ cervical samples detecting EMCA [2,7] and these still show positive predictive values (PPVs) far lower than those for cervical lesions.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that liquid-based cytology, which leads to a reduction of blood and inflammatory cells and better cellular and nuclear preservation, can improve the recognition and detection of EMCA [4,5,6]. However, there are only a small number of studies in the English literature on SurePath™ cervical samples detecting EMCA [2,7] and these still show positive predictive values (PPVs) far lower than those for cervical lesions.…”
Section: Introductionmentioning
confidence: 99%
“…The cellular arrangement, pattern of cell spread and the background of the smear helps in diagnosing the origin of tumor cells involving the cervix. [ 2 ] Extra-uterine malignancies are also known to metastasize in the cervix and are rarely detected in cervical samples. [ 3 ] We wish to highlight in this report that a metastatic tumor to cervix or tumor involving endocervical canal can lead to direct sampling of the tumor by the endocervical brush or Cervex brush used for taking cervical sample.…”
Section: Discussionmentioning
confidence: 99%
“…A comprehensive recent work reviewed multiple aspects on the detection of uterine glandular lesions by SurePath in a Bethesda reporting environment [21], while other available SurePath cytology-histology correlation studies offer important considerations. However, they focus on a specified aspect of performance (detection rate in endometrial carcinomas [22]), use a mixed ThinPrep-SurePath pool of cases without comparison between the two technologies [23], or report cytology findings in a non-Bethesda reporting environment, making the findings less applicable to laboratories adhering to Bethesda guidelines [24-26]. …”
Section: Discussionmentioning
confidence: 99%